Exploring practical issues in children’s anthropometric measurements: A qualitative descriptive study involving Indonesian health professionals and community health workers - Wanda, Dessie; Astuti, Astuti; Adawiyah, Robiyatul; Syaiful, Afifah Ayu; Azizah, Latifah Fajri Nur; Azkiyati, Ade Maya; Huda, Mega Hasanul (Belitung Nursing Journal, 2025)
Background: Anthropometric measurements during early childhood are critical as they represent the initial stages at which nutritional status is determined. Practitioners who measure children’s growth must have similar and adequate skills in anthropometric measurement to ensure the validity of data regarding children’s nutritional status, particularly concerning stunting prevalence. Objective: This study aimed to explore the measurement practices conducted by community health workers (CHWs) in Indonesia, who are responsible for providing data related to children’s growth and, consequently, their nutritional status. Methods: A qualitative descriptive design was employed using online focus group discussions ranging from 1 to 1.5 hours. Data were collected from ten health professionals and eight CHWs, with analysis performed using thematic analysis. Results: Four themes emerged: barriers to measurement accuracy, varied skills in measurement, mothers’ behavior influenced by children’s reactions, and strategies for dealing with traumatized children. Conclusion: Practical issues that arose during routine anthropometric measurements included the reliability of measurements, the skill levels of examiners, the interplay between mothers’ and children’s reactions, and approaches to managing traumatized children during measurements. To effectively enhance integrated health posts (Posyandu) services, it is crucial to maintain calibrated, validated equipment and implement comprehensive training with periodic refreshers for CHWs. Additionally, improving facility infrastructure, fostering CHWs’ communication skills, and simplifying child-friendly measurement procedures will collectively optimize service quality, promote cooperation, and strengthen community trust.